2022
DOI: 10.1111/dar.13441
|View full text |Cite
|
Sign up to set email alerts
|

Health harms of non‐medical prescription opioid use: A systematic review

Abstract: Issues. Non-medical prescription opioid use (NMPOU) contributes substantially to the global burden of morbidity. However, no systematic assessment of the scientific literature on the associations between NMPOU and health outcomes has yet been undertaken. Approach. We undertook a systematic review evaluating health outcomes related to NMPOU based on ICD-10 clinical domains. We searched 13 electronic databases for original research articles until 1 July 2021. We employed an adaptation of the Oxford Centre for Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 196 publications
(265 reference statements)
0
4
0
Order By: Relevance
“…6,14,15 Many pharmaceuticals are associated with drug-induced death, and these may be prescribed or used nonmedically/illicitly, especially OA. 16,17 Use of opioids depresses respiration and may be a direct cause of death. 18 Sedatives like benzodiazepines and benzodiazepinerelated drugs may interact with opioids and increase the risk of death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,14,15 Many pharmaceuticals are associated with drug-induced death, and these may be prescribed or used nonmedically/illicitly, especially OA. 16,17 Use of opioids depresses respiration and may be a direct cause of death. 18 Sedatives like benzodiazepines and benzodiazepinerelated drugs may interact with opioids and increase the risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…Many pharmaceuticals are associated with drug‐induced death, and these may be prescribed or used nonmedically/illicitly, especially OA 16,17 . Use of opioids depresses respiration and may be a direct cause of death 18 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent national survey conducted in China showed that 17.6% of Chinese school children and adolescents were identi ed as having EBPs [12]. A systematic review showed that NMUPD can also cause several adverse mental health outcomes, including neurotic, stress-related and somatoform disorders, intimate partner violence and so on [13]. Despite there have been su cient studies demonstrated the association between NMUPD and mental disorders, previous study usually focused on speci ed aspects of EBPs [14] or mainly took opioids misuse [15,16] into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…At present, geographical and practice variations in opioid prescribing are high [ 5 , 6 ], potentially indicating inappropriate use but complicating a thorough evaluation of the exact societal burden. Nevertheless, there is a confirmed risk for nonfatal overdose, morbidity and mortality [ 7 , 8 ]. In addition to other harms such as cardiovascular and endocrine complications, chronic opioid use is also associated with opioid use disorder (OUD) development [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%